Analysis of the Demographic Bonus Phenomenon in the Province of North Kalimantan - Ariani Ariani; Charitin Devi; Wong Sing Yun (Yayasan Vifada Cendikia Indonesia, 2025)
Purpose: This study investigates the role of the demographic bonus in shaping economic growth and labor market outcomes in North Kalimantan Province. Specifically, it examines its effects on GRDP, labor force participation rate (LFPR), and open unemployment rate (OUR), while contributing to the limited empirical evidence at the sub-provincial level and offering implications for evidence-based regional policy. Research Design and Methodology: This study employs a quantitative descriptive approach using secondary data from the Central Bureau of Statistics (CBS) for the period 2018–2023. The unit of analysis covers regencies and cities in North Kalimantan Province. The study examines one independent variable (demographic bonus) and three dependent variables: gross regional domestic product (GRDP), labor force participation rate (LFPR), and open unemployment rate (OUR). Data analysis techniques include descriptive analysis, sign test, and panel data regression using the Common Effect Model (CEM), Fixed Effect Model (FEM), and Random Effect Model (REM). The best model is selected through Chow, Hausman, and Lagrange Multiplier tests. Classical assumption tests are also conducted to ensure the validity of the model. Findings and Discussion: The results show that the demographic bonus has a significant effect on gross regional domestic product (GRDP), the labor force participation rate (LFPR), and the open unemployment rate (OUR). Implications: This research indicates the need for government policy strategies in utilizing the demographic bonus to improve the quality of human resources and develop work programs that can absorb labour optimally.